Physical restraint in mental health nursing: A concept analysis - Junrong Ye; Chen Wang; Aixiang Xiao; Zhichun Xia; Lin Yu; Jiankui Lin; Yao Liao; Yu Xu; Yunlei Zhang (Elsevier, 2019)
Objective: Physical restraint is frequently used in medical services, such as in mental health settings, intensive care units and nursing homes, but its nature varies in different institutions. By reviewing related literature, this study aims to clarify the concept of physical restraint in mental health nursing. Method: Three databases (PubMed, PsycINFO and CINAHL) were retrieved, and Walker and Avant's concept analysis method was used to analyze the concept of physical restraint in mental health nursing. Results: Physical restraint is a coercive approach that enables the administration of necessary treatment by safely reducing the patient's physical movement. It should be the last option used by qualified personnel. Antecedents of physical restraint are improper behavior (violence and disturbance) of patients, medical assessment prior to implementation and legislation governing clinical usage. Consequences of physical restraint are alleviation of conflict, physical injury, mental trauma and invisible impact on the institution. Discussion: This study defined the characteristics of physical restraint in mental health nursing. The proposed concept analysis provided theoretical foundation for future studies. Keywords: Concept analysis, Mental health services, Physical restraint, Qualitative study, Walker and Avant's model